Effective Strategies on Learning Arabic for Children - Sokip, Sokip (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Arabic learning can take place at various ages of either children, adolescents or adults. Learning Arabic is something needed for especially Muslim because it is important in Muslim life. This paper will explain about the Arabic learning strategy for children. This is important to discuss because children need special strategies in learning for their ages. In collecting information, the writer uses library research method, which is done by comparing several literary sources, especially those that are the main source of discussion to discuss about the existing problems. Then, as the result, language learning is a help to determine how, and how well, learners learn a foreign language. There are many variations on learning strategy. Arabic learning strategies for children include playing, singing, telling stories, projects, demonstration, and conversation. By using the suitable and fun strategy, children can develop their potential well and effectively. The selection of learning strategies depends on children’s ages and characteristics.